HR practices, boredom, and leadership effects on workplace procrastination: English - Kristiani, Dernita; Tanady, Hendy (Jurnal Mantik, 2025)
This study aims to analyze the role of Developmental Human Resources Practices (DHRP) on Employee Workplace Procrastination (EWP) through Boredom at Work (BW) as a mediator, and to assess the influence of Exploitative Leadership (EL) and Self-Leadership (SL) as moderating variables. Using a census of 206 employees at the Bengkalis Correctional Institution (Dec 2024–Jan 2025), this study tests how Developmental Human Resource Practices (DHRP) shape Employee Workplace Procrastination (EWP) via Boredom at Work (BW), and whether Exploitative Leadership (EL) and Self-Leadership (SL) condition these links. A quantitative design with PLS-SEM was employed. DHRP significantly lowers BW yet shows a positive direct association with EWP; BW mediates the DHRP and EWP relationship. EL strengthens the impact of DHRP on BW, whereas SL does not moderate the BW and EWP path, suggesting limited buffering in highly standardized, low-autonomy settings. The findings advance work-design and self-regulation perspectives by incorporating negative affect into the boredom procrastination mechanism and by testing dual moderators in a public-sector corrections context using a full-population census. Managerially, competency-based DHRP, task enrichment/rotation, and safeguards against exploitative leadership can reduce boredom and improve productivity; strengthening DHRP can reduce procrastination overall directly and via lower BW. Future research should examine task autonomy and digital work-design features, explore serial mediation, and extend the setting across regions and public organizations